ESTAÇÃO AGROMETEOROLÓGICA EXPERIMENTAL AUTOMATIZADA E INTEGRADA A SOFTWARES PARA CÁLCULO DE ESTIMATIVAS DE DORMÊNCIA EM PESSEGUEIROS E VIDEIRAS - Pasternak, Wilian Diogo (2016)
The dormancy period of a plant consists of the period during which its development is suspended, being inactive. In some cases, the breakdown of dormancy does not occur naturally, requiring the break of this period, through the application of chemical or natural products. However, monitoring air temperature and relative humidity data specifically in the production environment has proven to be an expensive process. Using agrometeorological stations of meteorological institutes does not return exact data of the plantation. This work contributes to the peach and grapevine dormancy period analysis process by presenting a low cost experimental agrometeorological station capable of collecting temperature and relative humidity data. Integrated to this station, a software is provided to calculate the period of dormancy in peach trees and vines using the Utah methods, North Carolina, Modified Utah, Modified North Carolina and Cold Units. The station was developed employing the Atmel ATmega 328P microcontroller. The software was developed using WebServices technology and the Java programming language. Two agrometeorological stations were designed and installed, one in Guarapuava and another in Ponta Grossa, both cities of the state of Paraná. The data collections at both stations were compared to other stations in the region and data were considered satisfactory. The softwares developed for the correct functioning of the station, as well as the software to calculate the period of dormancy in peach trees and vines, return correct and adequate data for decision making.